Local Elites as Collaborative Networks: A Systematic Literature Review Analysis of Their Capabilities and Roles in Regional Development - Tarom, Muhamad; Aksuo, Muhammed (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
Local elites play a central role in regional development, yet the existing literature is fragmented on the economic and political aspects of electoral politics without providing a comprehensive explanation of their capabilities in creating high-performance governance and holistic development achievements. This study aims to analyse the multidimensional role of local elites in building collaboration and mobilising community participation to achieve quality governance. Using a systematic literature review method guided by PRISMA, this study analysed 10 selected articles from the Scopus database identified through the keywords "local elites", "regional development", and "political participation". The findings reveal that local elites are not a single entity, but rather a collaborative network of political, economic and religious elites. Each acts as a change agent, facilitator, mediator and resource enabler. The synergy between these elites, facilitated by effective communication and visionary leadership, is key in creating collaborative governance and increasing community participation. However, this study has limitations due to the limited scope of the literature and does not involve primary empirical data. The implication is that governments and stakeholders need to recognise the complex role of local elites and encourage collaborative leadership models involving formal and non-formal elites to improve accountability and effectiveness of local development.